RISE: New road-side speed display signs in reducing speeding problem in Malaysia / Dr Khairul Khaizi Mohd Shariff - Mohd Shariff, Khairil Khaizi (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Encouraging road users to follow the speed limit is vital as speeding causes one-third of fatal road accidents in Malaysia.